Pre-professional practice strategies and profile of the graduate of the comprehensive child development degree in an institute, Ecuador 2024. - Fernandez Unuzungo, Giovanni David (2025)
The study "Strategies for Pre-professional Practices and Graduate Profile in the Early Childhood Development Program at an Institute in Ecuador, 2024" assesses the effectiveness of a methodological strategies program aimed at enhancing graduate profiles. Employing a quantitative approach and a pre-experimental design, it analyzed responses from 35 students through surveys conducted before and after an educational intervention. Descriptive and inferential statistics, including the Mann-Whitney U test, indicated significant improvements in graduate profile dimensions and methodological strategies post-intervention. Although progress was made, ongoing challenges were identified, suggesting the need for more sustained program application. The study concludes that structured implementation of methodological strategies substantially improves student professional development and recommends institutionalizing such interventions to ensure educational quality and strengthen comprehensive training. Additionally, Cohen’s d effect size and confidence intervals were calculated to assess the practical significance of the findings.